Effect of different packaging materials on shelf life of Oyster Mushroom (Pleurotus spp.) - Ambatkar, Avinash R; Kumar, P Arun (Mushroom Research, 2016)
Mushroom fruit bodies have been known as a food source for thousands of years used in the preparation of many products such as pickles, mushroom vegetable salads, etc. However, due to short shelf-life, the produce remains acceptable for few hours only. Hence, in order to increase the storage life of the mushroom a study was carried out by using different packaging materials like PP, PVC and PET pouches and stored under different storage conditions. The results obtained from the above study has revealed that, the shelf life of the mushrooms has increased to 18 days under the refrigeration condition by using the polyethylene terepthalate packaging material and the quality analysis after the storage period showed that, colour (L* value, 64.23), PLW (5.54 %), hardness (149.7 gf), nutritional parameters of protein (25.83 %), fat (1.94 %), fibre (9.31%), ash (10.35 %) and organoleptic score (7/9) and microbial load (4.19Ã—10 cfu/g). The statistical analysis has showed the significant difference between the packaging material and storage days with all the quality parameters analysed in the present study.Â